**Answer:**

x³ + 2x² -3x +6

**Step-by-step explanation:**

We need to find the polynomial whose roots are ,

Say of we have zeroes as , α , β and γ , then the polynomial is ,

=> p(x) = k[ (x - α ) ( x - β) ( x - γ) ]

- where k is constant. Substituting the respective values , we have ,

=> p(x) = k [ ( x - (-2)) ( x - √3) ( x -√3)]

=> p(x) = k[ (x+2)(x² - 3)]

=> p(x) = k[ x(x² - 3) + 2(x² - 3) ]

=> p(x) = k[ x³ - 3x + 2x² - 6 ]

**=****>**** ****p(****x)**** ****=**** ****k[**** ****x³**** ****+**** ****2****x****²**** ****-**** ****3x**** ****-**** ****6**** ****]**** **

<h3>

**<u>Hence </u>****<u>the</u>****<u> </u>****<u>cubic </u>****<u>polynomial</u>****<u> is</u>****<u> </u>****<u>x³</u>****<u> </u>****<u>+</u>****<u> </u>****<u>2</u>****<u>x</u>****<u>²</u>****<u> </u>****<u>-</u>****<u> </u>****<u>3x</u>****<u> </u>****<u>+</u>****<u> </u>****<u>6</u>****<u> </u>****<u>.</u>**</h3>

**Answer:**

Step by Step Solution

More Icon

STEP

1

:

Equation at the end of step 1

STEP

2

:

3s2 - 2s + 1

Simplify ————————————

s2 - s + 2

Trying to factor by splitting the middle term

2.1 Factoring 3s2 - 2s + 1

The first term is, 3s2 its coefficient is 3 .

The middle term is, -2s its coefficient is -2 .

The last term, "the constant", is +1

Step-1 : Multiply the coefficient of the first term by the constant 3 • 1 = 3

Step-2 : Find two factors of 3 whose sum equals the coefficient of the middle term, which is -2 .

-3 + -1 = -4

-1 + -3 = -4

1 + 3 = 4

3 + 1 = 4

Observation : No two such factors can be found !!

Conclusion : Trinomial can not be factored

**Step-by-step explanation:**

<h2>Answer:-</h2>

First, **we**** ****need**** ****to**** ****add**** ****up**** ****the**** ****x****.**

We know that 4+8 = 12, so

Now, equating it to y,

Now, if I multiply on both sides,

I get,

Now, as 12 got cancelled , I got the final answer as

Hope it helps :)

1. We need to get rid of those pesky parentheses. We do this by distributing the 3.

2. We need to get "n" by itself, so we add 9 to both sides.

3. Add like terms.

4. Now, we need to get rid of the -9, so we divide both sides by -9. Remember that dividing by negative numbers changes the direction of the "greater than or equal to" symbol.

5. We divide, and the negatives cancel.

I wrote the answer both ways so that I could tell what the number line needed to look like.

Answer: 26.34

Step-by-step explanation: